Voluntary disclosure of information when firms are uncertain of investor response - Suijs, Jeroen (Journal of Accounting and Economics, 2007)
A firm may prefer not to disclose its private information if it is uncertain of investor response. In the setting under consideration, a firm needs to acquire capital from an investor. The investor can choose to invest in the firm, the risk free asset or in some alternative risky investment opportunity. It is shown that in a partial disclosure equilibrium, the firm discloses average information and withholds bad and good information. Disclosure of average information arises to attract the investor's capital away from the risk free asset.